The effect Of Employee Engagement and Emotional Intelligent on Organizational Commitment by Job Satisfaction as Mediate Variable Case in Employee Of Islamic Education Institution - Fatmah Bagis; Akhmad Darmawan; Mastur Mujib Ikhsani; Purnadi Purnadi (Jurnal Ilmiah Ekonomi Islam, 2021)
This study explain about the effect employee engagement and emotional intelligence on organizational commitment where job satisfaction is used as mediation variable. The method used in this study is case study on employee of Islamic education institution in Purwokerto. Questionnaires were administered to 100 employees from the management level to the staff level as the respondent. The analysis PLS (Partial Least Square) were used in this study. The results showed that Employee Engagement has no significant effect on Job Satisfaction, Emotional Intelligence has significant effect on Job Satisfaction. The results also showed that Job Satisfaction and Emotional Intelligence has no significant effect to organizational commitment, Employee Engagement has significant effect on organizational commitment. And the result showed that Job Satisfaction cannot mediate between Employee Engagement on Organizational Commitment, also cannot mediate Emotional Intelligence on Organizational Commitment.